Igre na snegu in smučanje v okviru gibalnega/športnega programa Mali sonček - Videmšek, Mateja (Šport (Ljubljana), 2018)
"Little Sun" (Mali sonček) is a sports programme that currently includes aroud 70.000 preschool children in Slovenia. It is intended for children aged two to six. The contribution demonstrates the importance of snow games and skiing which are among the key activities of the preschool children involved in the four levels of programme: Blue, Green, Orange and Yellow Little Sun. Levels systematically upgrade and supplement each other.
Keywords: igre na snegu; Mali sonček; predšolski otroci; smučanje; športna vzgoja